2016
DOI: 10.1002/gcc.22368
|View full text |Cite
|
Sign up to set email alerts
|

Expressional profiling of prostate cancer risk SNPs at 11q13.5 identifies DGAT2 as a new target gene

Abstract: A total of nine non-coding variants on 11q13.5 predispose men to prostate cancer (PrCa). rs200331695 within the EMSY intron is associated with aggressive PrCa and two high linkage disequilibrium (LD) groups of single-nucleotide polymorphisms (SNPs) in the intergenic region are associated with PrCa death. Here, the cis-effect of the SNPs on gene expression using expression quantitative trait loci analysis was investigated. The regulatory potential was screened in prostate tumors (n = 41) and in whole blood (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…EMSY is a putative target gene of miR‐653‐5p, and its oncogene role in cancers has been reported . In the current study, we demonstrated that EMSY was negatively regulated by miR‐653‐5p and EMSY silence led to attenuation of CC cell growth.…”
Section: Discussionsupporting
confidence: 60%
“…EMSY is a putative target gene of miR‐653‐5p, and its oncogene role in cancers has been reported . In the current study, we demonstrated that EMSY was negatively regulated by miR‐653‐5p and EMSY silence led to attenuation of CC cell growth.…”
Section: Discussionsupporting
confidence: 60%
“…This does not appear to be cancer specific. We found this paradoxical since several studies have shown that DGAT2 overexpression inhibits cell proliferation [ 10 , 31 , 35 ].…”
Section: Resultsmentioning
confidence: 88%
“…NCBI does not list clinical significance for any of the eight SNPs nor could we find any literature describing the phenotypes of these alleles. However, one publication does report several intergenic SNPs associated with decreased DGAT2 expression, which promotes predisposition to prostate cancer [ 35 ]. We investigated expression data for DGAT2 mutations (see Section 3.7 ) and indeed, one of the alleles (R218W, rs528376420) appears to show increased expression levels, though the results are highly variable and not statistically significant under our analysis.…”
Section: Resultsmentioning
confidence: 99%